Efek Ekor Jas dan Identifikasi Partai Politik dalam Pemilu Serentak 2019 di Bali - Kadek Dwita Apriani (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
This study is to see the effect of tail suits on the political choices of Balinese people who are known to have the highest identification of political parties in Indonesia ahead of simultaneous elections (pemilu serentak) in 2019. The method used is quantitative research methods with 1,120 respondents spreading across all regenciess/cities in Bali. The sampling technique applied was multistage random sampling, so the margin of error was 3%. The results of this study indicate the tail coat effect present in the community which has a strong identification of political parties. It's just that the tail coat effect reads smaller than ID party in the political choices of the Balinese people.